Evaluating culinary students’ safety awareness through pre- and post-test assessment of immersive hazard learning exposure - Abdullah, Asniyani Nur Haidar; Mokhtar, Mohd Khalid; Mustafa AlbakrI, Ikmal Faiq Albakri; Janarthanan Nambiar, Reshmahdevi; Saad, Mazni (RSIS International, 2025)
Commercial kitchens pose significant occupational risks, with a high incidence of staff injuries due to the dynamic and hazardous nature of the work. Traditional safety training often falls short in preparing workers for these real-world scenarios due to its passive, classroom-based approach. To bridge this critical gap, this study developed a mobile-based 360° panoramic immersive learning platform aimed at improving hazard awareness in commercial kitchen environments. The research contribution is a novel, accessible, and highly effective safety training solution that leverages immersive technology to address a long-standing challenge in occupational safety. The system was implemented using Unity3D, incorporating high-resolution 360° images captured with an Insta360 ONE X2 camera, and was accessible via both immersive (Google Cardboard VR) and non-immersive mobile modes. A quantitative methods approach involving 30 culinary students was used to evaluate system usability and training effectiveness. Usability testing showed strong performance across all dimensions (use, learnability, efficiency, and satisfaction), with mean scores from 4.27 to 4.70 out of 5, indicating the application was intuitive and efficient. Pre- and post-test comparisons revealed a substantial improvement in hazard identification, with average scores increasing from 29.33 to 83.67, demonstrating significant learning gains and competency standardization. Furthermore, 73.3% of participants preferred the immersive VR mode for enhanced spatial awareness, while 26.7% favored the non-immersive option for its accessibility. These findings underscore the potential of 360° panoramic immersive learning as a practical, engaging, and scalable solution for safety training in commercial kitchens